Cardiovascular risk factors associated with polymyalgia rheumatica and giant cell arteritis in a prospective cohort: EPIC-Norfolk Study. (19th July 2019) - Yates, Max; Luben, Robert; Hayat, Shabina; Mackie, Sarah L; Watts, Richard A; Khaw, Kay-Tee; Wareham, Nick J; MacGregor, Alex J
Abstract: Objectives: PMR and GCA are associated with increased risk of vascular disease. However, it remains unclear whether this relationship is causal or reflects a common underlying propensity. The aim of this study was to identify whether known cardiovascular risk factors increase the risk of PMR and GCA. Methods: Clinical records were examined using key word searches to identify cases of PMR and GCA, applying current classification criteria in a population-based cohort. Associations between cardiovascular risk factors and incident PMR and GCA were analysed using Cox proportional hazards. Results: In 315 022 person years of follow-up, there were 395 incident diagnoses of PMR and 118 incident diagnoses of GCA that met the clinical definition. Raised diastolic blood pressure (>90 mmHg) at baseline/recruitment was associated with subsequent incident PMR [hazard ratio=1.35 (95% CI 1.01, 1.80) P =0.045], and ever-smoking was associated with incident GCA [hazard ratio=2.01 (95% CI 1.26, 3.20) P =0.003]. Estimates were similar when the analysis was restricted to individuals whose diagnoses satisfied the current classification criteria sets. Conclusion: PMR and GCA shares common risk factors with vascular disease onset, suggesting a common underlying propensity. This may indicate a potential for disease prevention strategies through modifying cardiovascular risk.